Critical experimental parameters related to the cytotoxicity of zinc oxide nanoparticles - Zhang, Yan (Springer Netherlands, 2014)
The increasing use of zinc oxide nanoparticles (ZnO-NPs) has raised concerns about their potential hazards to human and environmental health. In this study, the characterization and cytotoxicity of two ZnO-NPs products (Z-COTE and Z-COTE HP1) were investigated. The zinc content of Z-COTE and Z-COTE HP1 was 82.5 ± 7.3 and 80.1 ± 3.5 %, respectively. Both ZnO–NP samples contained sub-cytotoxic levels of iron and copper, and silicon was detected from the surface coating of Z-COTE HP1. All samples were highly agglomerated, and the primary particles appeared as variable polyhedral structures. There was no significant difference in size distribution or average diameter of Z-COTE (53 ± 23 nm) and Z-COTE HP1 (54 ± 26 nm). A dose-dependent cytotoxicity was observed 24 h after exposure to ZnO-NPs, and monocytes were more sensitive than lung epithelial cells or lymphoblasts in both human and mouse cells. There was a significant difference in cytotoxicity between nano- and fine-forms, but only at the threshold cytotoxic dose with cellular metabolism assays. Compared to uncoated ZnO-NPs, the surface coating with triethoxycaprylylsilane marginally attenuated cellular oxidative stress and protected cellular metabolic activity. These results demonstrate the importance of model cell type, dose selection, and cytotoxicity assessment methodology to accurately evaluate the potential toxicity of various nanoparticles in vitro.